Via crucis. 2 - Bacardí Moreau, Emilio, 1844-1922 (Barcelona : Linkgua-Digital, 2019)
Vía Crucis tells of the splendor and demise of the coffee industry through the eyes of an immigrant family. The story takes place during the revolutionary period of 1868-1878, showing the misfortunes of Cuban society after the cry of Yara to the Pact of the Trench. Emilio Bacardi breathed the historical background outlined in his work and is therefore a direct witness to what was experienced at that stage of the struggle for independence in the city of Santiago. The narrator effectively achieves subtlety in his character portraits and provides context for the conflicts of the story. Unencumbe.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2021. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Cuba -- History -- Insurrection, 1868-1878 -- Fiction; Santiago de Cuba (Cuba) -- History -- Fiction; Cuba -- Historia -- Insurrección, 1868-1878 -- Ficción.; Santiago de Cuba (Cuba) -- Historia -- Ficción.; Libros electrónicos.